Influence of Integrated Organic and Inorganic Fertilizer Application on Yield and Nutrient Uptake by Okra (Abelmoschus esculentus L.) in a Moderately Saline Soil: Influence of Integrated Organic and Inorganic Fertilizer - Zaman, S M Shariar; Nuralom, Md; Hossain, Mohammad Zaber; Islam, Md Sanaul (South Asian Journal of Agriculture, 2025)
Integrated use of organic and inorganic fertilizers is now an indispensable part of sustainable agriculture. A pot experiment was carried out at the experimental site of Soil, Water and Environment Discipline, Khulna University, Bangladesh during the period of November to January (Rabi season) to evaluate the influence of interactive application of organic and inorganic fertilizers on growth, yield and nutrient uptake parameters of okra (Abelmoschus esculentus L.). In this study, “BARI Dherosh-1” variety of okra was used. The experiment was laid out in Completely Randomized Design (CRD) with six treatments (T0= Control, T1= Inorganic fertilizers, T2= Cow dung, T3= Vermicompost, T4= Cow dung + Inorganic fertilizers, T5= Vermicompost + Inorganic fertilizers) and three replications under each treatment. The data recorded from different agronomic parameters were statistically analyzed to find out the significant difference in growth, yield and nutrient uptake of okra as induced by different combinations of fertilizer application at 60 days after sowing. The integrated effects of inorganic and organic fertilizer were observed in case of yield and nutrient uptake parameters. Combined application (T4 and T5) produced higher fruit yield and higher NPK uptake by Okra. It suggests that farmers can benefit more by the integrated input management practices than single use of either inorganic or organic amendment. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 78-88